Strict Liability as a Counterbalance to the Principle of Error in Indonesian Criminal Law - Ahmad Rofiq; Pujiyono Pujiyono (Fakultas Hukum, Universitas Internasional Batam, 2022)
This study wants to reveal how the criminal law policy in formulating the principle of strict liability now and in the future. This research is included in the type of normative juridical research. The data collection technique in this research is in the form of literature study. The data obtained were analyzed by analytical descriptive. The results of this study indicate that the current criminal law policy in formulating the principle of strict liability can be found in several Indonesian laws and foreign laws with several formulation models. The strict liability principle in the RKUHP as a counterbalance to the principle of error does not provide more complete arrangements regarding the limits of criminal acts that can be subject to strict liability, besides that there is no regulation regarding defense as one of the characteristics of the formulation of the strict liability principle. The results of the comparative study concluded that the application of the principle of strict liability in the RKUHP requires limits, measures, and defense regarding which actions can be applied with strict liability considering that the principle of strict liability serves as a counterweight to the principle of 'no crime without fault'.